Time Management on Audit Effectiveness with the ‎Moderating role of Auditor Independence and Work ‎Complexity - Nazanin Bashirimanesh; Solmaz Shojaee; Zohreh Arefmanesh (پژوهش‌های تجربی حسابداری, 2025)
Auditors are always looking to manage their time to improve audit ‎effectiveness. In the current research, Time management on audit ‎effectiveness with the moderating role of auditor independence and ‎work complexity. The statistical population of the research includes ‎Members of the Chartered Accountants Society; whose number is ‎‎216. And the time domain of the research is the first six months of ‎‎1402. The individual characteristics examined by the auditors ‎included their gender, level of education, and their age status. To ‎measure the variables of the research, it was a questionnaire tool ‎‎(created and adapted by the researcher). Research findings show that ‎time management has a direct impact on audit effectiveness‏.‏‎ Also, ‎the auditor's independence has a direct impact on the effectiveness ‎of the audit‏.‏‎ However, the complexity of the work has a negative ‎effect on the effectiveness of the audit‏.‏‎ However, auditor ‎independence has a direct impact on the relationship between time ‎management and audit effectiveness‏.‏‎ However, the complexity of ‎work has a negative effect on the relationship between time ‎management and audit effectiveness.‎